TINJAUAN GEOGRAFI PENGRAJIN KAIN PERCA - Azam Sah Roni; Sumadi Sumadi; Nani Suwarni (JPG (Jurnal Penelitian Geografi), 2013)
This study was aimed to find Geography review of artisans in the village of Rag Clothes in Sukamulya District, Banyumas regency, Pringsewu in 2012. The pressure points of the study were on the availability of raw materials, marketing, labor, capital, transportation and income patchwork craftsmen.The method used in this research was descriptive method; the object of study was a review of geographic crafts patchwork by data sources of the patchwork craftsmen. Collecting data was by using field observation techniques and structured interviews. Data analysis used percentages as a basis for interpretation and description.The results of this study show that: (1) 6 people craftsmen (54.54%) said raw material patchwork crafts in last 1 month is not easily obtained, and 5 craftsmen (45.45%) said raw material patchwork craft in 1 readily available last month. (2) There were Craftsmen which stated their marketing was current in the last 1 month amounted to 7 people (63.63%), while stating noncurrent marketing consists of 4 people (36.36%). (3) 11 people craftsmen (100%) expressed easily in obtaining employment. (4) 11 people craftsmen (100%) stated that the capital was very supportive in patchwork craft production activities. (5) 11 people craftsmen (100%) stated that the existence of means of transport was very supportive. (6) The total income patchwork artisans in the village in the last 1 month Sukamulya is Rp42.415.000, -. Average income across craftsman is Rp3.855.900, -. Highest income amounted Rp.6.500.000, - and the lowest income amounted Rp2.0450.000, -.Keywords: Economic Geography.